2019
DOI: 10.1007/s00429-019-01901-0
|View full text |Cite
|
Sign up to set email alerts
|

Parsing rooms: the role of the PPA and RSC in perceiving object relations and spatial layout

Abstract: The perception of a scene involves grasping the global space of the scene, usually called the spatial layout, as well as the objects in the scene and the relations between them. The main brain areas involved in scene perception, the parahippocampal place area (PPA) and retrosplenial cortex (RSC), are supposed to mostly support the processing of spatial layout. Here we manipulated the objects and their relations either by arranging objects within rooms in a common way or by scattering them randomly. The rooms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 121 publications
(221 reference statements)
2
13
0
Order By: Relevance
“…Two participants did not show any significant results for the right FFA, five for the left FFA, one for the right pSTS, two for the left pSTS, and four for the left RSC. These proportions adhere to previous studies 44 46 . These participants were excluded from the respective analyses.…”
Section: Methodssupporting
confidence: 91%
“…Two participants did not show any significant results for the right FFA, five for the left FFA, one for the right pSTS, two for the left pSTS, and four for the left RSC. These proportions adhere to previous studies 44 46 . These participants were excluded from the respective analyses.…”
Section: Methodssupporting
confidence: 91%
“…Contrary to faces and bodies, however, the individual parts of a scene are not so straightforward to define, and the reviewed work has used an arguably quite coarse approach to define arbitrary parts of a scene. In reality, scenes vary in more intricate ways and across a multitude of dimensions, including typical distributions of low-and mid-level scene properties (Groen et al, 2017;Nasr et al, 2014;Watson et al, 2014), the category and locations of objects contained in the scene (Bilalic et al, 2019;Kaiser et al, 2014;Kim & Biederman, 2011), relationships between objects and the scene context (Faivre et al, 2019;Mudrik et al, 2010;Preston et al, 2013;Võ & Wolfe, 2013), and scene geometry (Harel et al, 2013;Henriksson et al, 2019;Kravitz et al, 2011;Lescroart & Gallant, 2019). At this point, a systematic investigation of how regularities across these dimensions contribute to efficient information analysis across natural scenes is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data suggest that this area might be viewpoint-sensitive showing stronger activations for objects, which were rotated in-depth, compared to objects, which were presented in frontal views. Previous studies had shown that the PPA was involved in the processing of objects that are relevant for spatial navigation (Aguirre et al, 1998; Janzen & van Turennout, 2004; Bilalić et al, 2019) with functional connections to the LOC (Baldassano et al, 2013). Our results with higher activations for in-depth rotated views in both objects and places ROIs, suggest that not only spatial processing of scenes but also of object stimuli in the PPA could facilitate complex object perception in earlier ventral stream areas.…”
Section: Discussionmentioning
confidence: 99%